2006
DOI: 10.1021/ie0509591
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Hydrogenation of Selected Nitro Compounds by Simultaneous Measurements of Calorimetric, FT-IR, and Gas-Uptake Signals

Abstract: The hydrogenation of nitrobenzene (NB) and ethyl-4-nitrobenzoate (NEE) over a Pd/carbon (1 wt % Pd) catalyst has been studied using a new small-scale, pressure-resistant reaction calorimeter (CRC.v4) fitted with an integrated infrared−attenuated total reflection (FT-IR−ATR) probe. This new calorimeter exploits the principles of power compensation and heat balance in combination with IR spectroscopy and on-line gas-uptake measurements. Thus, the reactions can be followed by three independent signals based on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…In this regard, spectroscopic techniques [10][11][12][13] as well as gas production [14] or uptake rate measurements [12,13] have been utilized.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, spectroscopic techniques [10][11][12][13] as well as gas production [14] or uptake rate measurements [12,13] have been utilized.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The selective reduction of a nitro group in an aromatic nitro compound in the presence of other reducible functionalities is generally approached by using a stoichiometric amount of a reducing agent. [7] However, such a process has a high E factor (defined as the ratio by weight of byproducts to the desired product) [8] and is not environmentally sustainable.…”
mentioning
confidence: 99%
“…Studer et al [3] took this disproportionation mechanism into account and cleverly added a second catalytic function (iron or vanadium salts in solution) to avoid the accumulation of the hydroxylamine by catalyzing the disproportionation of the hydroxylamine with the nitroso intermediate to give the corresponding aniline. On the other hand, Visentin et al [1] concluded on the basis of a combination of calorimetric, FTIR-ATR (attenuated total reflectance), and gas-uptake signals with Pd/C as catalyst that the results of Makaryan and Savchenko would be consistent with a direct hydrogenation route in which hydroxylamine is accumulated (Scheme 3).…”
mentioning
confidence: 99%
“…4 Over TiO 2 , supported nano-sized gold particles show high chemoselectivity. 4 While mechanistic and kinetic behaviour is extensively reported for the hydrogenation over Pd/C, [5][6][7][8] only little is known for Au/TiO 2 and what is happening on the catalyst surface is still ambiguous. [9][10][11] Understanding of reaction kinetics and mechanisms is crucial to design new catalysts and to optimise industrial processes.…”
mentioning
confidence: 99%
“…1). Based on simultaneous in situ infrared, calorimetric, and gas-uptake monitoring Visentin et al 8 confirmed the direct route pathway but nitrosobenzene was not analytically evidenced in the liquid phase. Moreover hydroxylamine was hardly detectable with nitrobenzene as reactant but its concentration increased significantly with ethyl-4-nitrobenzoate as reactant.…”
mentioning
confidence: 99%